African migrants and stress coping strategies in Australia: Implications for social work. (November 2022) - Ikafa, Irene; Hack-Polay, Dieu; Walker, Janet; Mahmoud, Ali B
This research investigates resettlement stress among African migrants in Australia and how migrants manage stress. The research used 30 semi-structured interviews with African migrants in Western Australia. Participants used various strategies, including reliance on family as a community and on God – usually constructed by alliance rather than kinship – to manage stress. The article's key contribution highlights the multilayered approach for social work to integration strategies for migrants. The study identifies three significant issues emerging: the importance of 'families' as community networks, the experience of discrimination and the significance of faith in God as crucial migrant support factors.